Research funding challenges in Brazil: researchers' perceptions from a public institution of professional education - Ribeiro, Cristhian Chagas; Costa, Woska Pires da; Sousa, Marcos de Moraes; Silva, Priscilla Rayanne E.; Miñana-Signes, Vicente; Noll, Matias (Frontiers in Research Metrics and Analytics, 2025)
IntroductionIn a global landscape characterized by intense competition and stringent funding criteria, researchers face the dual challenges of limited resources and high demand for innovation—a challenge that Brazil is no exception to. This study aimed to explore the perceptions, barriers, and challenges faced by researchers during the project submission process for approval by funding agencies, with a focus on schools within the Federal Network of Professional, Scientific, and Technological Education Institutions.MethodsA quantitative cross-sectional approach was used to examine the characteristics of researchers at a Brazilian institution in 2023. The sample comprised eighty three researchers who completed an online questionnaire containing eighty three questions on demographic characteristics, factors associated with project submission and approval, and reasons for non-submission or non-approval. The data were analyzed using descriptive statistics, including the Kolmogorov—Smirnov, Pearson's chi-square, and Mann—Whitney U-tests, followed by post hoc analysis and Yates' correction. Logistic regression was applied using the backward elimination method, and significant parameters (p < 0.20) free from multicollinearity were selected.ResultsThis study revealed that most researchers were men (61.4%) with doctoral degrees (91.6%), highlighted the critical role of proposal clarity and relevance in the project evaluation process. Gender (p = 0.011) and academic level (p = 0.025) were significant factors influencing project submission rates, with Brazilian National Council for Scientific and Technological Development (CNPq) fellows and researchers involved in graduate programs submitting more projects. The participants identified “search for funding” and “desire to expand research impact” as their primary motivations while citing “complex funding calls” and “funding limitations” as major barriers. Additionally, age and the number of children were found to affect project approval (p ≤ 0.018), with “proposal clarity” and “researchers' experience” having been critical factors for submission approval (p ≤ 0.03).ConclusionThe study results highlighted a gender disparity, with lower participation among women, and identified key factors influencing project submission, including the search for funding, curriculum development, and structural challenges. Additionally, the findings suggest the adoption of gender-sensitive and early-career grant criteria, targeted support for underrepresented researchers, and flexible mechanisms for those with caregiving responsibilities. These findings underscore the importance of public policies and institutional strategies in promoting equitable and inclusive funding opportunities.